Math Educational Game (GEMA) Based on CAI (Computer Assisted Instruction) in Learning Simple Counting for Mentally Impaired Students - Dico, Allan Maulid; Hastuti, Wiwik Dwi; AM, M Shodiq (Department of Special Education, 2023)
Counting is a basic skill in mathematics. Counting skills need to be taught in early childhood. The mentally retarded have problems in mastering the ability to count. This study aims to describe the effect of using CAI-based mathematics education game (GEMA) media in learning simple arithmetic for mentally retarded students. A total of five subjects were students with mild mental retardation at Special School C Autism Kedungkandang State. In the study using the pre-experimental method in the form of one group pretest and posttest design, the data were obtained through the results of the pretest and posttest. Then the data is processed through analysis of hypothesis testing using the Wilcoxon Signed Rank Test technique. The results of the study explained that the average value of the pretest and posttest. each worth 51 and 81. With the results of the hypothesis test obtained the value of Asymp.Sig. (2-tailed) of 0.041, it can be concluded that H1 is accepted and H0 is rejected. Thus, the CAI-Based Mathematical Education Game (GEMA) has an effect on improving simple arithmetic skills in mentally retarded students.